(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The purpose of the study was to find out the changes in the common hematological parameters in patients (n=998) of acute viral hepatitis caused by hepatitis E virus from April to May, 2018. The mean hemoglobin level was 13.5 g/dL. However, seven patients were found to have hemoglobin level <11.0 g/dL. The mean red cell count was 4.5 x 1012/L. The mean packed cell volume was 40.6%. The mean white blood cell count was 7.1 x 109/L. However, leucopenia was found in 8 cases. The mean platelet count was 186.2 x 109/L. Among the hematological changes associated with hepatitis E virus infection, thrombocytopenia is a notable finding.